2019
DOI: 10.3390/molecules24244537
|View full text |Cite
|
Sign up to set email alerts
|

Nano-(Q)SAR for Cytotoxicity Prediction of Engineered Nanomaterials

Abstract: Although nanotechnology is a new and rapidly growing area of science, the impact of nanomaterials on living organisms is unknown in many aspects. In this regard, it is extremely important to perform toxicological tests, but complete characterization of all varying preparations is extremely laborious. The computational technique called quantitative structure-activity relationship, or QSAR, allows reducing the cost of time-and resource-consuming nanotoxicity tests. In this review, (Q)SAR cytotoxicity studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 85 publications
0
31
0
Order By: Relevance
“…The computational technique helps to reduce the costs associated with labor, resources, and time in nanotoxicity assessments [ 82 ]. QSAR modeling is an efficient method of predicting the biological activity or toxicity of chemical substances on the basis of mathematical statistics and knowledge of machine learning ( Figure 2 ).…”
Section: Category Of In Silico Modelsmentioning
confidence: 99%
“…The computational technique helps to reduce the costs associated with labor, resources, and time in nanotoxicity assessments [ 82 ]. QSAR modeling is an efficient method of predicting the biological activity or toxicity of chemical substances on the basis of mathematical statistics and knowledge of machine learning ( Figure 2 ).…”
Section: Category Of In Silico Modelsmentioning
confidence: 99%
“…The calculation of the quasi‐SMILES model using the Monte Carlo equation provides ample statistical parameters. [ 98 ] In this case, the cytotoxicity calculation endpoint is the percentage of viability of the cells. In another case, i.e., an in vitro ML‐based algorithm, as shown in Figure , it was shown that single‐walled CNTs (SWCNTs) can amend the cellular motility and biological chirality of the cells, an anomaly that can be related to abnormal in vivo fetal development.…”
Section: Theoretical and Computational Ab Initio Tools To Address Safmentioning
confidence: 99%
“…Quasi‐SMILES was used to represent the physicochemical properties and experimental conditions: diameter, length, surface area, in vitro toxicity assay, cell line, exposure time, and dose. [ 60 ] The quasi‐SMILES‐based nano‐QSAR model calculation using Monte Carlo method, provided sufficient statistical parameters. In this case, the endpoint of cytotoxicity measurement is the cell viability (%).…”
Section: Models Predicting Colloidal Properties As Determinant To Nanmentioning
confidence: 99%
“…It was also demonstrated that the RF approach is applicable to modeling the cytotoxicity of silica. [ 60 ] Later, better nano‐QSAR models based on quasi‐SMILES were built using CORAL software with high determination coefficients (0.8–0.95). [ 65 ]…”
Section: Models Predicting Colloidal Properties As Determinant To Nanmentioning
confidence: 99%